The Influence of ASEAN Agreement on Transboundary Haze Pollution for Emission Changes in Indonesia - Muhamad Ferdy Firmansyah; Nanang Rusliana; Siti Sarawati Johar; Haikal Zulian Maulana; Zahra Firdausa Sunarya (CV. Literasi Indonesia, 2022)
Environmental degradation is one of the many environmental problems that need to be faced by every country in the world. Both developed and developing countries can find environmental degradation problems in various conditions and phenomena. One of the environmental problems in Southeast Asia is related to smog. Indonesia is one of the countries with high cases of smog pollution, this is because the vast forest area with massive land clearing makes forest fires frequent. respond. The ASEAN Agreement on Transboundary Haze Pollution is an agreement to control haze pollution that occurs in the Southeast Asian region. This study uses secondary data originating from the Indonesia Central Statistics Agency (BPS) with a quantitative method approach. This study seeks to find the phenomenon of environmental pollution, economy, and emission developments in Indonesia. It was found that energy emissions, FOLU, and forest fires were the three emissions that were not affected by the ASEAN Agreement on Transboundary Haze Pollution policy. The policy that Indonesia needs to take is to improve energy emission, fire disaster and FOLU control.